(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-157-165 Abstract. The article deals with the possibilities of integrating the educational content of the Mineralogical Museum of the Sergo Ordzhonikidze Russian State Geological Prospecting University into the system of teaching Russian to foreign geologists. The relevance of this work is determined by the practical significance of such integration in the development of professional disciplines by foreign students, as well as the need to train specialists who can effectively communicate in a professional multicultural environment. Integration of museum exhibits enables students to delve deeper into the content of academic courses, enhances their motivation to assimilate study materials, and cultivates interest in the history of Russian science and culture. The authors examine concrete methods of utilizing practical assignments aimed at developing lexical-grammatical skills, enhancing conversational abilities, and broadening the horizons of learners. Special emphasis is placed on the development of didactic materials that allow for the use of museum collections within the framework of the Geology curriculum. The study analyzes the characteristics of how foreign audiences perceive specific terminology and cultural heritage reflected in mineralogical and petrographic exhibitions. The practical value of the research lies in proposals for improving the program of teaching Russian language, as well as recommendations for activating self-study activities among foreign students. Key words: museum practices, Russian as a foreign language, technical university, Mineralogical Museum